ARAH PEMBAHASAN RISIKO INVESTASI AKTIVA RIIL DALAM BUKU AJAR AKUNTANSI MANAJEMEN DAN AKUNTANSI BIAYA - Arief Suadi (Journal of Indonesian Economy and Business (JIEB), 1998)
Out of 16 American textbooks on management accounting and costaccounting published during the period of 1956 - 1995, only sixIf such a trend exists, accounting professors are relieved because the threat ofacademic disparity between accounting students and that of business administrationwill diminish. Furthermore, eventually accounting professors will need not to takeremedial actions. The research finds that there is an upward trend in the discussionof risk in management accounting and cost accounting text books.Kata kunci: bahasan risiko dalam akuntansi